Whole genome analysis of Rhizopus species causing rhino-cerebral mucormycosis during the COVID-19 pandemic - Michael, Joy Sarojini; Venkatesan, Manigandan; Ninan, Marilyn Mary; Solaimalai, Dhanalakshmi; Sumanth, Lydia Jennifer; Varghese, Lalee; Kurien, Regi; Varghese, Rinku Polachirakkal; C, George Priya Doss (Frontiers in Cellular and Infection Microbiology, 2023)
Mucormycosis is an acute invasive fungal disease(IFD) seen mainly in immunocompromised hosts and in patients with uncontrolled diabetes. The incidence of Mucormycosis increased exponentially in India during the SARS-CoV-2 (henceforth COVID-19) pandemic. Since there was a lack of data on molecular epidemiology of Mucorales causing IFD during and post COVID-19 pandemic , whole genome analysis of the Rhizopus spp isolated during this period was studied along with detection of mutations that are associated with antifungal drug resistance .A total of 50 isolates of Rhizopus spp were included in this prospective study , which included 28 from patients with active COVID-19 disease, 9 from patients during the recovery phase and 13 isolates from COVID-19-negative patients. Whole Genome Sequencing(WGS) was performed for the isolates and the denovo assembly was done with the Spades assembler. Species identification was done by extracting the ITS gene sequence from each isolate followed by searching Nucleotide BLAST. The phylogenetic trees were made with extracted ITS gene sequences and 12 eukaryotic core marker genes sequence respectively to assess the genetic distance between our isolates. Mutations associated with instrinsic drug resistance to Fluconazole and Voriconazole were analysed.All 50 patients presented to the hospital with acute fungal rhinosinusitis. These patients had mean HbA1c of 11.2%, and serum ferritin of 546.8ng/ml .Twenty five patients had received steroids . By WGS analysis 62% of the Rhizopus species were identified as R. delemar . Bayesian Analysis of Population Structure (BAPS) clustering categorized these isolates into five different groups, of which 28 belong to group 3, 9 into group 5, 8 under group 1. Mutational analysis revealed that in the CYP51A gene, 50 % of our isolates had frameshift mutations along with 7 synonymous mutations and 46 % had only synonymous mutations whereas in the CYP51B gene 68 % had only synonymous mutations and 26 % did not have any mutations.WGS analysis of Mucorales identified during and post the COVID-19 pandemic gives insight into the molecular epidemiology of these isolates in our community and establishes newer mechanisms for intrinsic azole resistance